Preparation method of composite coating with high structural stability, repeated use and ultra-high temperature ablation resistance
By introducing chopped fibers and modifiers into the ultra-high temperature ceramic coating, the problem of mismatch in the thermal expansion coefficient and insufficient binding force of the coating at high temperatures is solved, and the structural stability and repeated ablation resistance of the coating are significantly improved, ensuring that the material can be reused at high temperatures.
Patent Information
- Application Number
- CN202311398144.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
The existing ultra-high temperature ceramic coatings have problems with mismatch in thermal expansion coefficient and insufficient binding force at high temperatures, resulting in unstable structure and easy to fall off during repeated ablation, affecting the reusable performance of the material.
By introducing chopped fibers into the coating, the thermal expansion coefficient of the coating is adjusted to make it close to the thermal expansion coefficient of the ceramic-based composite material substrate. By adding modifiers such as La-based and Y-based, the phase transition of high-melting oxides and the volatility of the glass phase are suppressed, thereby enhancing the structural stability and bonding strength of the coating.
It significantly improves the structural stability of the coating and the bonding strength with the substrate, extends the repeated ablation resistance of the coating, and ensures that the material can be reused at temperatures above 2500°C.
Smart Images

Figure CN119899051A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ultra-high temperature ceramic coatings, and in particular relates to a method for preparing a highly structurally stable, reusable, ultra-high temperature ablation-resistant composite coating. Background Art
[0002] Carbon / carbon and fiber-reinforced ceramic matrix composites have the advantages of good thermal shock resistance, small thermal expansion coefficient, high thermal conductivity, good chemical stability, etc., and have good mechanical properties at high temperatures, making them ideal materials for hot end components of advanced high-speed aircraft. However, as advanced high-speed aircraft develop towards high Mach number flight speeds and reusability, higher requirements are placed on hot end component materials. Current carbon / carbon and fiber-reinforced ceramic matrix composites face ablation and oxidation corrosion during service, and it is difficult to meet the demand for reusability at temperatures above 2500°C. Therefore, further improving the material's resistance to repeated ablation has become a major engineering need that needs to be urgently addressed.
[0003] Currently, the two commonly used technologies of substrate modification and coating protection enable the material to generate an oxide layer during the ablation process, isolating oxygen erosion, thereby improving the ablation resistance of the material. However, the modifiers introduced by the substrate modification technology (such as oxide components such as TiO2, Al2O3, and Y2O3) are prone to physical / chemical reactions with the substrate at high temperatures, reducing the high-temperature mechanical properties of the substrate, which is not conducive to the reuse of the material. Therefore, constructing a modified ultra-high temperature ceramic coating on the surface of the material is an effective means to ensure the high-temperature mechanical properties of the substrate and improve the ablation resistance of the material. Currently, the commonly used coatings are mainly composite ceramic coatings composed of ultra-high temperature ceramics (Zr-based borides, Hf-based borides, Ta-based borides, carbides) and SiC. Ultra-high temperature ceramics are oxidized to high-melting point oxides (ZrO2, HfO2, etc.) at high temperatures. As a network structure in the coating, SiC is oxidized to SiO2 glass phase, interspersed in the network structure, and plays a role in healing pores and isolating oxygen. However, there are problems of thermal expansion coefficient mismatch and insufficient bonding between the current simple ultra-high temperature ceramic coating and the fiber-containing substrate. Macroscopically, there are problems of thermal expansion coefficient mismatch and insufficient bonding between the simple ultra-high temperature ceramic coating and the fiber-containing substrate, which causes thermal stress to be generated by ablation during repeated service and reduces the structural stability of the coating, resulting in cracks in the coating and falling off, thereby reducing the reusability of the substrate. Microscopically, the ultra-high temperature ceramic coating currently used undergoes phase change under repeated thermal action by high temperature oxidation to generate high melting point oxides, which cause phase change stress, resulting in intercrystalline cracks and oxide layer shedding. In addition, the SiO2 glass phase volatilizes severely during repeated ablation, affecting the reusability of the material. Therefore, it is of great significance to improve the coating's repeated ablation resistance by improving the coating's structural stability, improving the preparation process, and improving the coating-substrate bonding strength, so that the coating generates a high-viscosity, uniformly distributed oxide layer during repeated ablation. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention aims to provide a method for preparing a highly structurally stable and reusable ultrahigh temperature ablation resistant composite coating, which mainly improves the material's resistance to repeated ablation by improving the structural stability of the coating and its oxide layer, and the coating-substrate bonding strength. The present invention is suitable for the preparation of multi-element ultrahigh temperature ceramic coatings on the surface of components, has a simple process, a controllable process, and low cost, and is suitable for components of various structures and sizes.
[0005] On the basis of the traditional ultra-high temperature ceramic coating, in order to solve the problem of insufficient structural stability of the traditional coating, the present invention selects short-cut fibers as the toughening component of the coating, adjusts the thermal expansion coefficient of the coating, and makes its thermal expansion coefficient close to that of the ceramic-based composite material substrate, thereby solving the problems of coating-substrate cracking caused by thermal expansion coefficient mismatch. In addition, by introducing a modifying component into the coating and inhibiting the phase change of the high melting point oxide in the coating, not only can the problem of insufficient high-temperature mechanical properties caused by directly introducing a modifier into the ceramic-based composite material substrate be avoided, but also the ablation resistance of the material can be ensured through this coating with high structural stability.
[0006] The present invention provides a method for preparing a reusable ultra-high temperature ablation resistant composite coating with high structural stability, comprising: (1) mixing ultrahigh temperature ceramic powder, modifier powder, dispersant and solvent to obtain a mixture; the ratio of ultrahigh temperature ceramic powder to modifier powder is: ultrahigh temperature ceramic powder accounts for 20 to 95 vol%, and modifier powder accounts for 5 to 80 vol%; (2) adding the chopped fibers into the mixture and obtaining a slurry by ultrasonic dispersion; (3) immersing the substrate in the obtained slurry so that the slurry is evenly coated on the surface of the substrate, and then drying and curing to form a coating on the surface of the substrate; (4) placing the coated substrate obtained in step (3) in an inert atmosphere for high-temperature heat treatment; (5) Densifying the coating after high-temperature heat treatment by precursor impregnation cracking or reactive infiltration to obtain a highly structurally stable, reusable, ultra-high temperature ablation-resistant composite coating; when densification is performed by precursor impregnation cracking, the modifier is at least one of a rare earth compound, a metal silicide, and a carbide; when densification is performed by reactive infiltration, the modifier is at least one of a rare earth compound, a metal silicide, a carbide, and a carbon source; preferably, the rare earth compound is YB4 and / or La2O3; the metal silicide is ZrSi2 and / or CrSi2; the carbide is SiC and / or Al4SiC4; the carbon source is sucrose or carbon powder.
[0007] The inventors have found that the thermal expansion coefficient mismatch between the coating and the substrate and the preparation process of the coating are the key factors affecting the structural stability of the coating, the bonding strength between the coating and the substrate, and the ablation resistance of the material. In addition, during the ablation process, the high-melting-point oxides generated by the ablation and oxidation of the coating undergo phase change and volatilization of the glass phase, which will reduce the protective ability of the oxide layer and cause the coating to have a reduced resistance to repeated ablation. Therefore, the present invention uses short-cut fibers as toughening agents to construct a composite coating, thereby reducing the thermal expansion mismatch between the coating and the fiber-containing substrate and improving the structural stability of the coating; by adding La-based, Y-based and other compound modifiers, La 3+ , Y 3+ Solid solution causes the high melting point oxide lattice to be distorted, thereby inhibiting the coating ablation oxide layer high melting point oxide phase transition; and La 3+ , Y 3+ After solid solution, the high melting point oxide has low growth momentum and is easy to form nanocrystals and disperse into the glass phase, thereby inhibiting the volatilization of the glass phase and increasing the viscosity of the glass phase, thereby improving the ablation resistance of the ablated oxide layer. Based on this, the repeated ablation resistance of the coating and material is improved.
[0008] Preferably, in step (1), the ultra-high temperature ceramic powder is at least one of Hf-based boride, Zr-based boride, Ta-based boride and carbide; preferably, the boride is HfB2 or ZrB2; the carbide is HfC and / or ZrC; The dispersant is at least one of phenolic resin, polyvinyl butyral, and polyvinyl pyrrolidone; The solvent is at least one of anhydrous ethanol, acetone, and ethyl acetate; More preferably, the proportion of the dispersant in the mixture is 1 to 15 vol%; and the solid content of the mixture is 20 to 80 vol%.
[0009] Preferably, in step (2), the length of the chopped fibers is 10 μm to 2 mm; and the content of the chopped fibers in the slurry is 5 to 30 vol%.
[0010] Preferably, in step (2), the chopped fibers are carbon fibers or silicon carbide fibers; preferably, the chopped fibers are chopped fibers having an interface layer on the surface; the interface layer is PyC, BN, SiC, or a composite interface layer thereof; the thickness of the interface layer is 0 to 900 μm, preferably 200 to 300 μm.
[0011] Preferably, in step (3), the substrate is a carbon / carbon composite material or a fiber-reinforced ceramic-based composite material; the fiber-reinforced ceramic-based composite material is at least one of an ultra-high temperature ceramic-based composite material, a C / SiC composite material, and a C / SiBCN composite material; preferably, the substrate is an ultra-high temperature ceramic-based composite material; more preferably, the ultra-high temperature ceramic-based composite material is C / ZrB2-SiC or C / HfC-SiC.
[0012] Preferably, in step (3), the drying temperature is 80-100° C. and the drying time is 6-12 h; The curing temperature is 130-200° C. and the curing time is 5-10 hours.
[0013] Preferably, in step (4), the high temperature heat treatment process is: the heat treatment temperature is 500-1200° C., the heat treatment time is 0.5-3 h; the heat treatment atmosphere is an inert atmosphere, preferably argon or nitrogen.
[0014] Preferably, in step (5), the precursor is at least one of polycarbosilane and ultra-high temperature ceramic precursor; the temperature of the impregnation pyrolysis is 800-1500° C., and the time is 0.5-6 h.
[0015] Preferably, in step (5), the reactive infiltration metal raw material is one or more of Si, Zr, Hf, HfSi2, ZrSi2, the infiltration temperature is 1000-1800°C, and the insulation time is 0.5-5h; the atmosphere used is nitrogen or argon.
[0016] Preferably, the thickness of the highly structurally stable, reusable, ultra-high temperature ablation-resistant composite coating is 0.1 to 3 mm; the difference in thermal expansion coefficient between the coating and the substrate at room temperature to 2000°C is less than 10%, preferably 1 to 5%; the bonding strength of the coating is ≥40 MPa, preferably 40 to 120 MPa; the linear ablation rate of the coating after a single 300 to 1200 s and 5 to 15 air plasma ablation at 1000 to 2600°C is less than 5 μm / s.
[0017] The traditional ultra-high temperature ablation resistant coating is a pure ceramic component, which is directly connected to the substrate. There is an obvious mismatch in thermal expansion coefficient between the composite substrate and the coating, which is easy to crack and fall off under heat. Moreover, the high-temperature oxidation of the traditional ultra-high temperature ceramic coating generates a high melting point oxide, which undergoes a phase change under repeated heat action, generating phase change stress, thereby causing intercrystalline cracks to cause the oxide layer to fall off. And the SiO2 glass phase volatilizes seriously during the repeated ablation process, affecting the reusability of the material. However, the present invention adjusts the thermal expansion coefficient of the coating through chopped fibers, so that its thermal expansion coefficient is close to that of the ceramic-based composite substrate, thereby solving the problems of coating-substrate cracking caused by thermal expansion coefficient mismatch. The coating is densified by precursor impregnation cracking and reaction infiltration, and the bonding strength between the coating and the substrate is improved; in the precursor impregnation cracking process, the liquid precursor can not only enter the pores in the coating, but also enter the pores in the composite substrate, thereby enhancing the bonding strength between the coating and the substrate; and the reaction infiltration process can also rely on the liquid phase alloy to fill the pores in the coating and the substrate, thereby enhancing the bonding strength between the coating and the substrate. By adding La-based, Y-based and other compound modifiers, La 3+ , Y 3+ Solid solution causes the high melting point oxide lattice to be distorted, thereby inhibiting the coating ablation oxide layer high melting point oxide phase transition; and La 3+ , Y 3+ The high-melting-point oxide after solid solution has low growth kinetics and is easy to form nanocrystals and disperse into the glass phase, thereby inhibiting the volatilization of the glass phase and increasing the viscosity of the glass phase, thereby improving the ablation resistance of the ablated oxide layer.
[0018] Beneficial effects:
[0019] Compared with the traditional preparation technology of ultra-high temperature ablation resistant coating, the present invention has the following advantages: 1) The present invention uses chopped fibers as tougheners to construct a composite coating, thereby reducing the thermal expansion mismatch between the coating and the fiber-containing substrate and improving the structural stability of the coating; 2) The coating is densified by precursor impregnation cracking or reactive infiltration, and the bonding strength between the coating and the substrate is improved; 3) The high melting point oxide phase transition of the coating ablation oxide layer is inhibited by adding a modifier, and the glass phase viscosity is increased, thereby improving the ablation resistance of the oxide layer. The preparation method of the present invention can greatly improve the structural stability of the ultra-high temperature ceramic coating, the bonding strength between the coating and the substrate, and can effectively improve the material's resistance to repeated ablation. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A preparation route map of the highly structurally stable and reusable ultrahigh temperature ablation resistant composite coating of the present invention; Figure 2 This is a schematic diagram of the structure of the highly structurally stable and reusable ultra-high temperature ablation resistant composite coating of the present invention; Figure 3The C containing the high structural stability and reusable ultra-high temperature ablation resistant composite coating of the present invention in Example 1 f / ZrB2-SiC based composites and C f / ZrB2-SiC substrate repeated ablation line ablation rate and ablation times at 2600℃. DETAILED DESCRIPTION
[0021] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.
[0022] In the present invention, the effect of improving the material's resistance to repeated ablation is achieved from the perspectives of reducing the difference in thermal expansion coefficients between the ultra-high temperature ceramic coating and the substrate, increasing the coating-substrate bonding strength, and improving the structural stability of the coating and its oxide.
[0023] The following is an exemplary description of a method for preparing a reusable ultra-high temperature ablation resistant composite coating with high structural stability provided by the present invention.
[0024] Preparation of the mixture. Ultra-high temperature ceramic powder, modifier powder, dispersant and solvent are mixed by ball milling to obtain a mixture. At least one of Hf-based boride (such as HfB2), carbide (such as HfC), Zr-based boride (such as ZrB2), Ta-based boride and carbide is selected as the ultra-high temperature ceramic component of the coating. At least one of rare earth compounds (such as YB4, La2O3, etc.), metal silicides (such as ZrSi2, CrSi2, etc.), carbides (SiC, Al4SiC4), and carbon sources (such as sucrose, carbon powder, etc.) is selected as the modifier component. The role of the carbon source is to react with the metal silicide to form carbides during the reaction infiltration process. If impregnation cracking is used to densify the coating later, since impregnation cracking can directly generate carbides, the carbon source is not used. At least one of phenolic resin, polyvinyl butyral, and polyvinyl pyrrolidone is selected as a dispersant. At least one of anhydrous ethanol, acetone, and ethyl acetate is selected as a solvent. The proportion of ultra-high temperature ceramic powder and modifier powder is: ultra-high temperature ceramic accounts for 20-95vol%, and modifier accounts for 5-80vol%; preferably, ultra-high temperature ceramic accounts for 40-60vol%, and modifier accounts for 5-20vol%vol%. Compared with ultra-high temperature components, modifiers and their oxides have low melting points and do not have ablation resistance. If there are too many modifiers, the modifier replaces the ultra-high temperature phase to become the main phase of the material matrix, resulting in insufficient ultra-high temperature components in the matrix, which will lead to a decrease in the ablation resistance of the material. The proportion of dispersant in the mixture is 1-15vol%. The solid content of the mixture is 20-80vol%, preferably 30-70vol%. If the solid content is too low, the viscosity of the mixture will be insufficient and it will be difficult to form; if the solid content is too high, the coating thickness will be too thick. The speed of the ball mill is 50-500r / min, and the time is 2-24h; preferably, the speed of the ball mill is 200-500r / min, and the time is 12-24h.
[0025] Selection and surface modification of chopped fibers. In the present invention, carbon fibers (C f ) or silicon carbide fiber as chopped fiber (SiC f ); the length of the chopped fibers is 10 μm to 2 mm. Preferably, the chopped fibers are chopped fibers with an interface layer on the surface, which can adjust the bonding strength between the fibers and the ceramic and relieve the thermal stress between the fibers and the ceramic. The interface layer is at least one of PyC, BN, SiC, or a composite interface thereof; the thickness of the interface layer is 0 to 900 μm. The interface layer can be prepared on the surface of the chopped fibers by the CVI method.
[0026] Preparation of slurry. Add the chopped fibers to the obtained mixture and obtain a uniformly dispersed slurry by ultrasonic dispersion. The conditions of ultrasonic dispersion are not limited, and it is preferable to be able to disperse the materials uniformly. The chopped fibers and the mixture are uniformly mixed by ultrasonic dispersion or other methods until there is no obvious precipitation and fiber clusters.
[0027] In an optional embodiment, the content of the chopped fibers in the slurry is 5 to 40 vol%, preferably 5 to 30 vol%. If the content of the chopped fibers is too low, the toughening effect on the coating will be lost. If the content of the chopped fibers is too high, the fibers will become the main phase of the coating and will be easily oxidized into holes during the ablation process, causing damage to the coating structure and affecting the oxidation resistance of the coating. The ultrasonic dispersion time is 1 to 8 hours.
[0028] Selection and preparation of substrate. In the present invention, a carbon / carbon composite material or a fiber-reinforced ceramic-based composite material is selected as the substrate, and the fiber-reinforced ceramic-based composite material is at least one of an ultra-high temperature ceramic-based composite material, a C / SiC composite material, and a C / SiBCN composite material; preferably, an ultra-high temperature ceramic-based composite material is selected as the substrate, such as C / ZrB2-SiC, C / HfC-SiC. The immersion time of the substrate in the slurry is 1 to 20 minutes. The substrate is immersed in the obtained slurry, and the substrate is pulled up so that the slurry is evenly coated on the surface of the substrate. After drying and curing, it is placed in an inert atmosphere for high-temperature heat treatment. For example, a substrate such as a carbon / carbon composite material, a fiber-reinforced ceramic-based composite material is immersed in the slurry, and after standing for 1 to 20 minutes, the substrate is pulled up so that the slurry is evenly coated on the surface of the substrate.
[0029] In an optional embodiment, the substrate surface coating slurry is placed in an oven at 80-100°C for drying for 6-12 hours, and cured at 130-200°C for 5-10 hours. Then, it is heat treated at 500-1200°C for 0.5-3 hours in an argon or nitrogen atmosphere to fully pyrolyze and debond the organic matter in the coating and cool it with the furnace.
[0030] Preparation of ultra-high temperature ablation resistant composite coating. The coating is densified by precursor impregnation cracking or reactive melt infiltration to obtain a highly structurally stable and reusable ultra-high temperature ablation resistant composite coating.
[0031] In an optional embodiment, the process parameters of the precursor impregnation cracking are: the precursor is at least one of polycarbosilane and ultra-high temperature ceramic precursor; the inert gas atmosphere is argon or nitrogen; the impregnation cracking temperature is 800-1500°C and the time is 0.5-6h. The impregnation cracking process is repeated until the coating is dense.
[0032] In the present invention, after a carbon source is added to the modifier, the coating is densified by reactive infiltration. Preferably, the proportion of the carbon source in the modifier is 5 to 20 wt%. The parameters of the reactive infiltration are: at least one of Si, Zr, Hf, HfSi2, and ZrSi2 is selected as the metal raw material, the inert atmosphere is argon or nitrogen, and the reactive infiltration is carried out at 1000 to 1800° C. for 0.5 to 5 hours to make the molten metal and the carbon source undergo a carbon thermal reduction reaction to obtain a densified coating.
[0033] The thickness of the highly structurally stable, reusable, ultra-high temperature ablation-resistant composite coating is 0.1 to 3 mm; the difference in thermal expansion coefficient between the coating and the substrate at room temperature to 2000° C. is less than 10%, preferably 1 to 5%; the bonding strength of the coating is ≥40 MPa, preferably 40 to 120 MPa; the linear ablation rate of the coating after a single 300 to 1200 s and 5 to 15 air plasma ablation at 1000 to 2600° C. is less than 5 μm / s.
[0034] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0035] Example 1
[0036] A method for preparing a reusable ultra-high temperature ablation resistant composite coating with high structural stability comprises the following steps: (1) Micron-sized HfB2 ultra-high temperature ceramic powder, micron-sized SiC modifier powder, phenolic resin dispersant, and anhydrous ethanol are used as raw materials and mixed uniformly by ball milling at 200 r / min for 24 hours to obtain a mixture. Among the micron-sized HfB2 ultra-high temperature ceramic powder and micron-sized SiC modifier powder, HfB2 accounts for 80 vol%, SiC accounts for 20 vol%. The solid content of the mixture is 70 vol%. The dispersant accounts for 10 vol% in the mixture; (2) CVI method is used to cut short C with a length of 200 to 500 μm. f Surface preparation of a PyC interface with a thickness of ∼500 μm; (3) The chopped fibers and the mixture are uniformly mixed by ultrasonic dispersion for 8 hours until there is no obvious precipitation and fiber clusters, to form a slurry. The chopped fibers are added to the mixture obtained in step (1), and a uniformly dispersed slurry is obtained by ultrasonic-assisted stirring. The chopped fiber content in the slurry is 30 vol%; (4) C f After the surface of the ZrB2-SiC substrate is coated with the slurry, it is placed in an oven at 100°C for 12 hours and cured at 180°C for 10 hours to form a coating. Then, it is heat treated at 800°C for 3 hours in an argon atmosphere to fully pyrolyze and debond the organic matter in the coating and then cooled with the furnace; (5) A polycarbosilane precursor is selected and the coating is impregnated for 5 hours using a vacuum impregnation method. The coating is then cracked for 4 hours at 1000° C. in an argon atmosphere. The impregnation and cracking process is repeated until the coating is dense to obtain the highly structurally stable and reusable ultra-high temperature ablation resistant composite coating.
[0037] The coating bonding strength is tested with reference to the tensile test method in the HB5476-1991 standard. The material ablation is tested using air plasma ablation. The working atmosphere is compressed air and nitrogen protective gas. An infrared thermometer is used to test the surface temperature at the center of the material ablation.
[0038] The thickness of the ultra-high temperature ceramic composite coating obtained in this Example 1 is 500 μm. At room temperature to 2000°C, the difference in thermal expansion coefficient between the coating and the substrate is 8%, the coating bonding strength is 42 MPa, and after 10 air plasma ablation tests at 2600°C, the coating structure is intact and has no shedding, and the linear ablation rate is less than 3 μm / s.
[0039] Figure 3 The figure is a relationship between the linear ablation rate and the number of ablation times of the Cf / ZrB2-SiC-based composite material containing the high structural stability and reusable ultra-high temperature ablation resistant composite coating of the present invention and the Cf / ZrB2-SiC substrate at 2600°C. It can be seen from the figure that the coating prepared by the present embodiment 1 can effectively improve the repeated ablation resistance of the C / ZrB2-SiC composite material; after 10 ablations, the linear ablation rate of the C / ZrB2-SiC composite material containing the coating is about 10% of the linear ablation rate of the C / ZrB2-SiC substrate.
[0040] Example 2
[0041] The method for preparing a reusable ultra-high temperature ablation-resistant composite coating with high structural stability in this embodiment 2 refers to that in embodiment 1, with the only difference being that in step (1), the ultra-high temperature ceramic powder is micron-sized HfC and ZrC powder, wherein the volume ratio of HfC to ZrC is 3:2.
[0042] The thickness of the ultra-high temperature ceramic composite coating obtained in this Example 2 is ~500μm, the difference in thermal expansion coefficient between the coating and the substrate is 6%, the coating bonding strength is 42MPa, and the coating structure is intact without falling off after 10 air plasma ablation tests at 2600°C, and the linear ablation rate is less than 4μm / s.
[0043] Example 3
[0044] The method for preparing a reusable ultra-high temperature ablation resistant composite coating with high structural stability in this embodiment 3 refers to that in embodiment 1, with the only difference being that in step (1), the modifier is a mixture of micron-sized SiC and micron-sized YB4 powder, and the volume ratio of YB4 powder to the modifier is 5 vol%.
[0045] The thickness of the ultra-high temperature ceramic composite coating obtained in this Example 3 is ~500μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 8%, the coating bonding strength is 43MPa, and after 10 air plasma ablation tests at 2600℃, the coating structure is intact and has no shedding, and the linear ablation rate is less than 3μm / s.
[0046] Example 4
[0047] The method for preparing a reusable ultra-high temperature ablation resistant composite coating with high structural stability in this embodiment 4 refers to that in embodiment 1, with the only difference being that in step (1), the modifier is a mixture of micron-sized SiC and micron-sized La2O3 powder, and the volume ratio of La2O3 powder to the modifier is 5 vol%.
[0048] The thickness of the ultra-high temperature ceramic composite coating obtained in this Example 4 is ~500μm. At room temperature ~2000°C, the difference in thermal expansion coefficient between the coating and the substrate is 7%, the coating bonding strength is 50MPa, and after 10 air plasma ablation tests at 2600°C, the coating structure is intact and has no shedding, and the linear ablation rate is less than 5μm / s.
[0049] Example 5
[0050] The method for preparing the reusable ultra-high temperature ablation resistant composite coating with high structural stability in this embodiment 5 refers to that in embodiment 1, with the only difference being that in step (2), the interface is a PyC / SiC composite interface, and the interface thickness is ∼800 μm.
[0051] The thickness of the ultra-high temperature ceramic composite coating obtained in this embodiment 5 is ~600μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 8%, the coating bonding strength is 45MPa, and after 10 air plasma ablation tests at 2600℃, the coating structure is intact without falling off, and the linear ablation rate is less than 4μm / s.
[0052] Example 6
[0053] The method for preparing the reusable ultra-high temperature ablation resistant composite coating with high structural stability in this embodiment 6 refers to that in embodiment 1, with the only difference being that in step (2), the chopped fibers are SiC fibers.
[0054] The thickness of the ultra-high temperature ceramic composite coating obtained in this embodiment 6 is ~600μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 8%, the coating bonding strength is 48MPa, and after 10 air plasma ablation tests at 2600℃, the coating structure is intact without falling off, and the linear ablation rate is less than 5μm / s.
[0055] Example 7
[0056] The method for preparing the reusable ultra-high temperature ablation resistant composite coating with high structural stability in this embodiment 7 refers to that in embodiment 1, with the only difference being that in step (3), the content of the chopped fibers in the slurry is 20 vol%.
[0057] The thickness of the ultra-high temperature ceramic composite coating obtained in this embodiment 7 is ~500μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 9%, the coating bonding strength is 42MPa, and after 10 air plasma ablation tests at 2600℃, the coating structure is intact without falling off, and the linear ablation rate is less than 5μm / s.
[0058] Example 8
[0059] The method for preparing the reusable ultra-high temperature ablation resistant composite coating with high structural stability in this embodiment 8 refers to that in embodiment 1, with the only difference being that in step (4), the substrate is a carbon / carbon composite material.
[0060] The thickness of the ultra-high temperature ceramic composite coating obtained in this embodiment 8 is ~500μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 9%, the coating bonding strength is 48MPa, and after 10 air plasma ablation tests at 2600℃, the coating structure is intact without falling off, and the linear ablation rate is less than 5μm / s.
[0061] Example 9
[0062] The preparation method of the reusable ultra-high temperature ablation resistant composite coating with high structural stability in this embodiment 9 refers to that in embodiment 1, with the only difference being that in step (5), the precursor is a ZrB2 ultra-high temperature ceramic precursor.
[0063] The thickness of the ultra-high temperature ceramic composite coating obtained in this embodiment 9 is ~500μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 5%, the coating bonding strength is 48MPa, and after 10 air plasma ablation tests at 2600℃, the coating structure is intact without falling off, and the linear ablation rate is less than 3μm / s.
[0064] Example 10
[0065] The method for preparing the high structural stability reusable ultra-high temperature ablation resistant composite coating in this embodiment 10 refers to that in embodiment 1, the only difference is that in step (1), the modifier is micron-sized SiC and carbon powder, wherein the carbon powder accounts for 10 vol% of the modifier. In step (5), ZrSi2 is selected as the infiltration alloy, and the coating is obtained by infiltration at 1500°C in an argon atmosphere.
[0066] The thickness of the ultra-high temperature ceramic composite coating obtained in this embodiment 10 is ~500μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 7%, the coating bonding strength is 46MPa, and after 10 air plasma ablation tests at 2600℃, the coating structure is intact and has no shedding, and the linear ablation rate is less than 5μm / s.
[0067] Comparative Example 1
[0068] In this comparative example 1, a HfB2-SiC coating is prepared on the surface of a C / ZrB2-SiC substrate by chemical vapor deposition (CVI): Hf-based reaction gas, B4C, and trichloromethylsilane are used as precursors, hydrogen is used as a carrier gas, the deposition temperature is 1200°C, and the deposition pressure is 20KPa, to prepare a HfB2-SiC coating on the surface of a C / ZrB2-SiC substrate, wherein HfB2 accounts for 80 vol% in the HfB2-SiC coating.
[0069] The thickness of the HfB2-SiC coating obtained in this comparative example 1 is ~500μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 20%, the coating bonding strength is 21MPa, and the coating structure falls off after 10 air plasma ablation tests at 2600℃, and the linear ablation rate is 15μm / s.
[0070] Comparative Example 2
[0071] The preparation method of the reusable ultra-high temperature ablation resistant composite coating with high structural stability in this comparative example 2 refers to that in Example 1, except that: in step (3), the content of the short-cut fibers in the slurry is 60 vol%.
[0072] The thickness of the ultra-high temperature ceramic composite coating obtained in this comparative example 2 is ~500μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 12%, and the coating bonding strength is 30MPa. After 10 air plasma ablation tests at 2600℃, the coating is loose and porous, exposing the substrate, and the linear ablation rate is 15μm / s.
[0073] Comparative Example 3
[0074] The preparation method of the reusable ultra-high temperature ablation resistant composite coating with high structural stability in this comparative example 3 refers to that in Example 1, the difference is that: in step (1), no modifier is added.
[0075] The thickness of the ultra-high temperature ceramic composite coating obtained in this comparative example 3 is ~500μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 8%, and the coating bonding strength is 25MPa. After 10 air plasma ablation tests at 2600℃, the coating surface has cracks and partially falls off, and the linear ablation rate is about 8μm / s.
[0076] Comparative Example 4
[0077] The preparation method of the reusable ultra-high temperature ablation resistant composite coating with high structural stability in this comparative example 4 refers to that in Example 1, except that: in step (1), the proportion of the SiC modifier in the micron-sized HfB2 ultra-high temperature ceramic powder and the micron-sized SiC modifier powder is 95 vol%.
[0078] The thickness of the ultra-high temperature ceramic composite coating obtained in this comparative example 4 is ~500μm. At room temperature ~2000℃, the difference in thermal expansion coefficient between the coating and the substrate is 10%, and the coating bonding strength is 25MPa. After 10 air plasma ablation tests at 2600℃, the coating surface has cracks and obvious shedding, and the linear ablation rate is about 10μm / s.
Claims
1. A method for preparing a reusable ultra-high temperature ablation resistant composite coating with high structural stability, characterized in that: include: (1) mixing ultrahigh temperature ceramic powder, modifier powder, dispersant and solvent to obtain a mixture; the ratio of ultrahigh temperature ceramic powder to modifier powder is: ultrahigh temperature ceramic powder accounts for 20 to 95 vol%, and modifier powder accounts for 5 to 80 vol%; (2) adding the chopped fibers into the mixture and obtaining a slurry by ultrasonic dispersion; (3) immersing the substrate in the obtained slurry so that the slurry is evenly coated on the surface of the substrate, and then drying and curing to form a coating on the surface of the substrate; (4) placing the coated substrate obtained in step (3) in an inert atmosphere for high-temperature heat treatment; (5) Densifying the coating after high temperature heat treatment by precursor impregnation cracking or reactive infiltration to obtain a highly structurally stable, reusable, ultra-high temperature ablation-resistant composite coating; If densification is carried out by precursor impregnation cracking, the modifier is at least one of rare earth compounds, metal silicides, and carbides; if densification is carried out by reactive infiltration, the modifier is at least one of rare earth compounds, metal silicides, carbides, and carbon sources; preferably, the rare earth compound is YB4 and / or La2O3; the metal silicide is ZrSi2 and / or CrSi2; the carbide is SiC and / or Al4SiC4; the carbon source is sucrose or carbon powder.
2. The preparation method according to claim 1, characterized in that: In step (1), the ultra-high temperature ceramic powder is at least one of Hf-based boride, Zr-based boride, Ta-based boride and carbide; preferably, the boride is HfB2 or ZrB2; the carbide is HfC and / or ZrC; The dispersant is at least one of phenolic resin, polyvinyl butyral, and polyvinyl pyrrolidone; The solvent is at least one of anhydrous ethanol, acetone, and ethyl acetate; More preferably, the proportion of the dispersant in the mixture is 1 to 15 vol%; and the solid content of the mixture is 20 to 80 vol%.
3. The preparation method according to claim 1 or 2, characterized in that: In step (2), the length of the chopped fibers is 10 μm to 2 mm; and the content of the chopped fibers in the slurry is 5 to 30 vol%.
4. The preparation method according to any one of claims 1 to 3, characterized in that The chopped fibers are carbon fibers or silicon carbide fibers; preferably, the chopped fibers are chopped fibers having an interface layer on the surface; the interface layer is PyC, BN, SiC, or a composite interface layer thereof; the thickness of the interface layer is 0 to 900 μm, preferably 200 to 300 μm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (3), the substrate is a carbon / carbon composite material or a fiber-reinforced ceramic-based composite material.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (3), the drying temperature is 80-100° C. and the time is 6-12 hours; the curing temperature is 130-200° C. and the time is 5-10 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (4), the high temperature heat treatment process is: the heat treatment temperature is 500-1200° C., the heat treatment time is 0.5-3 h; the heat treatment atmosphere is an inert atmosphere, preferably argon or nitrogen.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (5), the precursor is at least one of polycarbosilane and ultra-high temperature ceramic precursor; the inert gas atmosphere is argon or nitrogen; the immersion cracking temperature is 800-1500° C., and the time is 0.5-6 hours.
9. The preparation method according to any one of claims 1 to 8, characterized in that: In step (5), the reactive infiltration metal raw material is one or more of Si, Zr, Hf, HfSi2, ZrSi2, the infiltration temperature is 1000-1800°C, and the insulation time is 0.5-5h; the atmosphere used is nitrogen or argon.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The thickness of the highly structurally stable, reusable, ultra-high temperature ablation-resistant composite coating is 0.1 to 3 mm; the difference in thermal expansion coefficient between the coating and the substrate at room temperature to 2000° C. is less than 10%, preferably 1 to 5%; the bonding strength of the coating is ≥40 MPa, preferably 40 to 120 MPa; the linear ablation rate of the coating after a single 300 to 1200 s and 5 to 15 air plasma ablation at 1000 to 2600° C. is less than 5 μm / s.
Citation Information
Cited By
Low-aluminum refined ladle brick and preparation method thereof
CN120398516A